Towards a Transformed Geography Curriculum: A Post-colonial Critique - Kudzayi Tarisayi (Universitas Djuanda, 2023)
The growing need to decolonize higher education has put pressure on geography educators to reform curricula and pedagogy. This literature review examines the history, rationale and pathways of curriculum decolonization with an emphasis on: 1) the history of calls to decolonize geography courses 2) arguments for why reform is needed and 3) examples of reforms in different contexts. A postcolonial framework clarifies why traditional curricula perpetuate marginalization and why transforming geographic education is crucial. It also highlights how teacher development focused on decolonization, local pedagogy and knowledge can facilitate reform. Overall, transforming geographic education to recognize excluded perspectives, knowledge and injustice is imperative but progress depends on empowering educators to envision and implement transformative reforms.